Bounce behaviors of double droplets simultaneously impact cold superhydrophobic surface. (July 2023) - Zhou, Xin; Wang, Hong; Wu, Junjun; Zhang, Qian; Zhu, Xun; Ding, Yudong; Chen, Rong; Liao, Qiang
Highlights: A three-dimensional extended enthalpy-porosity solidification model is established and the deviation between experiments and simulations is within 10%. Five impact-freezing modes are reported on cold superhydrophobic surface. The contact time of partial coalescence rebound mode is shorter than that of the single-droplet impact at room-temperature. The interaction between the droplets increases the likelihood of ice adhesion. Abstract: The real physical process of ice formation involves multiple droplets rather than a single isolated one. Clarifying the mechanism of multi-droplet impact-freezing is important for designing functional surfaces for anti-icing. The rebound behavior of double droplets simultaneously impinging on a cold superhydrophobic surface (SHS) was investigated experimentally and numerically, which is a classical simplified case in multi-droplet impingement. We found five impacting-freezing modes, including no-coalescence rebound (NCR), partial-coalescence rebound (PCR), complete-coalescence rebound (CCR), no-coalescence adhesion (NCA) and coalescence adhesion (CA). Moreover, the effects of horizontal spacing, impact velocity and surface temperature on the spreading factor and uprising sheet height during the impacting-freezing process were also analyzed. The contact time of PCR mode is even shorter than that of a single droplet impact at room temperature, which is verified and explained in our results. However, as the surface temperature decrease, the behavior of the coalescing droplet transitions from PCR to CCR and CA mode. The increase in Weber number could cause the adhesion of double droplets. Moreover, the horizontal spacing strongly affects the coalescing process. Multiple droplet impact-freezing will lead to severe icing on the substrate due to multiple droplets interaction involved. This study is beneficial for anti-icing and de-icing technologies.